2014
DOI: 10.1186/1471-2458-14-974
|View full text |Cite
|
Sign up to set email alerts
|

Trends and prevalence of overweight and obesity in primary school aged children in the Republic of Ireland from 2002-2012: a systematic review

Abstract: BackgroundThe prevalence of childhood overweight and obesity in developed countries appears to be levelling off. As trends in childhood obesity prevalence have not been examined over the past decade in the Republic of Ireland, this systematic review aims to compile and synthesise all available information on the prevalence of overweight and obesity in primary school aged children between 2002 and 2012.MethodsSystematic review of published and grey literature containing data on objectively measured height and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 35 publications
5
43
0
Order By: Relevance
“…The results here confirm the findings in Keane et al (2014). The figures for normalized BMI (relative to the obesity threshold) show that it falls by about 1.5% while the rate of obesity falls slightly.…”
Section: Data and Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The results here confirm the findings in Keane et al (2014). The figures for normalized BMI (relative to the obesity threshold) show that it falls by about 1.5% while the rate of obesity falls slightly.…”
Section: Data and Resultssupporting
confidence: 91%
“…Perry et al (2009) showed that weight for children in Ireland had increased disproportionately compared to height, thus leading to a rise in BMI, over the period from the late 1940s to the mid 2000s. Keane et al (2014) provide a comprehensive review of more recent evidence concerning trends and prevalence of obesity among primary school aged children in Ireland, covering the period from 2002 to 2012. After carefully reviewing a number of studies, they confined their analysis to 14 studies which met their inclusion criteria.…”
Section: The Measurement Of Obesity In Children and Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Easy access to affordable, healthy foods at school is recommended in obesity management strategies (2)(3)(4) , and with 20-25 % of Irish adolescents currently overweight or obese (5)(6)(7)(8) , there is increasing pressure on the education sector to play a role in management and prevention. This situation is not unique to Ireland; the availability of low-nutrient, energy-dense foods in schools and the environments close to schools is well documented in international literature (9)(10)(11)(12)(13)(14)(15)(16)(17)(18) .…”
mentioning
confidence: 99%
“…There are some specific issues, relating to social, economic and lifestyle factors, for example, the relatively large number of children living in poorer households (1); a high prevalence of both overweight and obesity in school children (2); a high prevalence of binge drinking (3); and poor mental health, with very high suicide rates both in male and female adolescents (4), all of which continue to challenge the Irish health services.…”
Section: Measures Of Health Here]mentioning
confidence: 99%